REPRESENTASI MAKNA DAN NILAI KARAKTER PADA MAJAS DALAM LIRIK LAGU JKT48: Representation of Meaning and Character Values in Metaphors in Jkt48 Songs - Melinda Kusuma Wardani Djapur; Anshari; Tuti Wijayanti (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This study, entitled ‘Representations of Meaning and Character Values in Figurative Language within JKT48 Song Lyrics’, is a descriptive qualitative study which aims to (1) describe the representations of meaning and character values in figurative language within JKT48 song lyrics, and (2) describe the representations of character values in figurative language within JKT48 song lyrics. The results of this study indicate that the representations of meaning in the figures of speech within the lyrics of JKT48 songs titled ‘Buah Masa Depan’, ‘Bunga Matahari’, ‘Apakah Kau Melihat Mentari Senja?’, and ‘Matahari Milikku’ include optimism, facing doubt, self-reliance, openness to feelings, mutual support, mutual respect, and loyalty in supporting friends. Furthermore, the character values represented by figures of speech in JKT48 song lyrics include hard work, honesty, independence, social awareness, friendliness/communication, love of peace, tolerance, and responsibility. The figures of speech that contribute to representing the meaning and character values throughout the lyrics of JKT48’s songs are metaphor, personification, depersonification, synecdoche, simile, hyperbole, paradox, hyperbole, interminus contradiction, oxymoron, parallelism, anticlimax, rhetoric, tautology, polysyndeton, and pleonasm